PENGARUH PENGGUNAAN METODE NUMBERED HEAD TOGETHER (NHT) BERBANTU PETA KONSEP TERHADAP HASIL BELAJAR IPS TERPADU SISWA KELAS VIII SEMESTER GENAP MTs NEGERI 1 LAMPUNG TIMUR - Gus Muchrozin; Triani Ratnawuri (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
Students have low graduation rate on KKM replicate mid semester IPS Integrated makes the need for research in class VIII C MTs Negeri 1 Lampung Timur. With various elements that support the learning process then students should be able to learn well. This provides the discourse that with various elements for learning fulfilled it can affect the mastery of concepts and improve student learning outcomes, and use the method of Numbered Head Together (NHT) aided concept map selected by the author because it is appropriate for this problem. The formulation of this research problem is